Entomopathogenic fungi associated with whitefly control: A review (Research, Society and Development, 2022)
Currently, the development and registration of a series of products based on Cordyceps fumosorosea and Beauveria bassiana have shown to be highly able to suppress and control whitefly under greenhouse and field conditions. However, some factors have weighed negatively on their use as slow action, low efficiency against adults and eggs, negative interaction with fungicides, and climatic limitations. Accordingly, studies have been developed to overcome those limitations, using several cultural practices to increase the efficiency of those organisms. Therefore, this review aims to list which entomopathogenic fungi have a control effect against Bemisia tabaci and what are the favourable conditions for this control. To that end, a literature review was carried out on scientific papers, analyzing studies with entomopathogenic fungi to control B. tabaci and those on the favourable environmental conditions for it, in addition to those that selected which instars are the most sensitive to the action of such control organisms. In conclusion, we may infer that B. tabaci can be managed by entomopathogenic fungi if the following measures are adopted: a) use against nymphal instars; b) use under favourable environmental conditions for the biological agents; c) use of application technology to increase the efficiency of the application of spores; and d) asynchronous application with fungicides. Furthermore, due to the innocuousness of these organisms, food and environmental security can also be increased.